Банда синего крокодила: [повесть] / Наталия Кузнецова - Кузнецова Наталия Александровна (Черный котенок, 2016)
Экземпляры: (20160428) / Инвентарный номер: 39222 / Цена: 161.00; 170.77 / Авт.знак: К 89 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6